Achievable rates of Gaussian cognitive interference channel with common interference. Issue 16 (17th September 2020) - Al‐Qudah, Zouhair; Darabkh, Khalid A.
Abstract : This study considers the Gaussian cognitive interference channel (IC), in which one of the two users operates in cognitive mode. In addition, to transmit its signal, the cognitive sender can cooperatively forward the primary signal to its destination, the primary receiver. Moreover, the transmission over this IC also experiences interference from a third source, which is commonly known as the common interferer source. To reduce the effect of both the primary signal and the common interference signal at the secondary destination, both the cognitive transmitter and its destination may have noisy complete (non‐causal) or partial (causal) knowledge of these signals. For this channel model, the achievable rate region is computed in which the availability of both the primary signal and the common interference signal at the cognitive transmitter and its destination can be (i) noisy non‐causal and (ii) causally estimated. The authors numerical results confirm that knowing both the primary signal and the common interference signal can significantly increase the achievable rate region. Indeed, the obtained achievable rate region is larger than the available bounds in the literature. Furthermore, representative numerical examples are also shown to demonstrate the value of the power allocation at the cognitive source.